Deconstructing learner engagement: An expanded construct model for higher education learners - Meral Şeker (International Journal of Assessment Tools in Education)
Despite the unanimous agreement regarding the positive outcomes of learner engagement, theorists and researchers draw attention to the disparate conceptualizations and structural models of “engagement” construct. The present study, in this respect, attempts to contribute to the development of a theoretical framework by suggesting a multidimensional overarching model for assessing higher education learner engagement. Following the descriptive research design, the study reports the initial model construction and validation results. The findings show significant differences from the earlier conceptualizations indicating a five-dimension model: academic-functional, cognitive, meta-cognitive, collaborative-social, and collaborative- academic engagement. While metacognitive engagement indicators form a distinct but integral dimension in the construct, the social dimension displays an idiosyncratic structure, implying that the multidimensional nature of the engagement construct has a situated nature. Pedagogical implications are discussed based on the engagement model validated.